Structure, Substructure, Hardness and Adhesion Strength of Multiperiod Composite Coatings MoN / CrN - Grankin, S. S.; Beresnev, V. M.; Sobol, O. V.; Stolbovoy, V. A.; Novikov, V. Yu.; Lytovchenko, S. V.; Nyemchenko, U. S.; Meylekhov, A. A.; Kovaleva, M. G.; Postelnyk, A. A.; Toryanik, I. N. (Sumy State University, 2015)
A comprehensive study of the influence of the thickness of the layers, Us and PN on the structural engineering to obtain high mechanical properties in multilayer composite MoN / CrN vacuum-arc coatings has been conducted by means of scanning electron microscopy with energy analysis, X-ray diffraction studies microindentation and scratch testing methods. It has been determined that in the studied Torr, the content of nitrogen in the coatings varies from 6.3 to 33 at. %, which leads even at the greatest nitrogen content to the formation of lower phase by nitrogen and isostructural CrN with the vacant sites in the nitrogen sublattice. The increase of thickness of the layers applied on the substrate in a stationary state promotes the increase of nitrogen content. Along with this, the lowest microdeformation and the average size of crystallites are formed at Ub = – 300 V, which defines the achievement of greater hardness of 35 GPa and high adhesion strength, which resists the destruction, Lc5 = 187.6 N.
Keywords: vacuum-arc coatings; multilayer coating; hard coatings; vacuum-arc deposition